Whole genome analysis of 26 bacterial strains reveals aromatic and hydrocarbon degrading enzymes from diverse environmental soil samples - Md Shakhawat Hossain; Brian Iken; Rupa Iyer (Scientific Reports, 2024)
Abstract Polycyclic aromatic compounds and petroleum hydrocarbons (PHs) are hazardous pollutants and seriously threaten the environment and human health. However, native microbial communities can adapt to these toxic pollutants, utilize these compounds as a carbon source, and eventually evolve to degrade these toxic contaminants. With this in mind, we isolated 26 bacterial strains from various environmental soil samples. Utilizing whole genome shotgun sequencing and analyses of these genomes revealed that they all belong to a single phylum with seven genera and sixteen species, and displayed variable genome sizes with CDS features, % GC contents, and GC skews. The analysis of genome annotation predicted genes/enzymes related to aromatic compound degradation, including the metabolism of homogentisate, salicylate and gentisate catabolism, benzoate, biphenyl, and phenylpropanoid compound degradation, and protocatechuate branch of beta-ketoadipate pathways. The majority of enzymes were found to belong to species Achromobacter pulmonis A (16%) & Achromobacter mucicolens (15%), Pseudomonas citronellolis (10%), and Comamonas thiooxydans (8%). Conversely, the highest number of hydrocarbon-degrading enzymes were found to be annotated in the species Pseudomonas citronellolis (13%), Comamonas thiooxydans (9%), Acinetobacter variabilis (7%), Pseudomonas aeruginosa, and Pseudomonas E sp002113165 (6%). These enzymes were categorized as dioxygenase, monooxygenase, hydroxylase, dehydrogenase, hydrolase, decarboxylase, aldolase, etc., and were predicted to function for benzoate, benzene, toluene, naphthalene, xylene, phthalate & terephthalate, anthranilate, protocatechuate & homoprotocatechuate, salicylate, aerobic & anaerobic gallate, and lignin subunit degradation, and catechol meta & ortho-cleavage pathways. In the future, molecular and biochemical characterization of these enzymes, together with strain assays for their capacity to degrade various pollutants, will help to improve the bioremediation process for environmental contaminations.